Visual meta-data in qualitative analysis. - Luther, Anne K (Digital Scholarship in the Humanities, 2018)
Dr Anne Luther is a researcher, curator, and software developer whose work examines the contemporary art market and data visualization in qualitative research. She received her PhD from Central Saint Martins College of Art and Design, London, and is currently a researcher at the Department for Modern Art History at the Institute of Art Studies and Historical Urban Studies at TU Berlin and at The Center for Data Arts at The New School in New York. Her PhD research presents a cultural analysis of contemporary art collecting and art production with an illustration of patterns that overlap in collecting and art production practices in contemporary art. The analysis shows how institutions, local context, social strategies, and prestige overlap in their influences on art production as a cause for collecting contemporary art. Her research in data visualization, qualitative methods, and data analysis emerged into the successful implementation of new software for qualitative research, The Entity Mapper. anneluther.info@AnneLuthera https://github.com/lutheranne